ADAPTING EFFECTIVE MARKETING MIX, POLICIES AND STRATEGIES DURING THE COVID-19 CRISIS - Panja, Anup Kumar (The journal of contemporary issues in business and government, 2021)
Coronavirus assault on worldwide level has tossed many difficulties to numerous areas what's more business isn't a special case here. It has shaken the economies of created, immature, and non-industrial nations. The point of this review is distinguished how organizations can adjust their marketing arrangements and methodologies during the COVID-19 emergency. The paper talks about the impacts of COVID-19 on consumer conduct and expound on the outcomes of this interruption for marketing methodologies.